The Effect of Carbon Emissions Disclosure on Company Value In The Energy Sector Listed on The Indonesian Stock Exchange - Resi Dwi Wulandari; Emillia Nurdin; Safaruddin Safaruddin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the effect of carbon emissions disclosure on firm value in energy sector companies listed on the Indonesia Stock Exchange during the 2022 to 2024 period. The research employs a quantitative approach using secondary data obtained from annual reports, sustainability reports, and financial statements. The sample consists of 15 energy sector companies selected through purposive sampling, resulting in 45 firm year observations. Firm value is measured using Price to Book Value, while carbon emissions disclosure is assessed through a Carbon Disclosure Index. Data analysis is conducted using panel data regression with EViews 12 following model selection and diagnostic testing procedures. The findings indicate that carbon emissions disclosure does not have a significant effect on firm value. The results suggest that investors in the Indonesian energy sector continue to place greater emphasis on financial performance indicators than on environmental disclosure information. Carbon disclosure appears to function primarily as a regulatory compliance mechanism rather than as a strategic signal capable of enhancing market valuation. The study contributes to the environmental accounting literature by providing evidence that the economic relevance of carbon disclosure remains limited in emerging capital markets and may require stronger disclosure quality and greater investor awareness to influence firm valuation.